XPS ANALYSIS OF DIAMOND-LIKE CARBON FILMS - Roman V. Pigulev; Konstantin I. Sidorov; Vitaliy A. Tarala; Sergey V. Lisitsyn; Elena N. Belyaeva; Maria V. Moskvicheva (Вестник Северо-Кавказского федерального университета)
The paper presents an analysis of the results of a study into diamond-like carbon films synthesized by plasma-chemical deposition from hydrocarbon sources: methane (СН4) and ethane (С2Н6). Analysis of the spectra of X-ray photoelectron spectroscopy was employed to study the effect that the synthesis conditions have on the structure and composition of amorphous carbon films.